Analisis Dampak E-Service Quality, Experiential Marketing, E-Trust, dan E-Security E-Branch BCA Terhadap Loyalitas Nasabah (Studi Kasus pada BCA KCP Gatot Subroto Malang) - Apsarini, Nabila Wahyu; Rizal, Mohammad; Novianto, Abdullah Syakur (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to examine the "Impact Analysis of E-Service Quality, Experiential Marketing, E- Trust, and E-Security of BCA's E-Branch on Customer Loyalty (Case Study at BCA KCP Gatot Subroto Malang)." This research employs a quantitative approach. The sample was collected through questionnaires using a purposive sampling technique, and Malhotra's formula was used to determine the sample size, which is the number of items multiplied by 5, resulting in a total sample of 100 respondents. The analysis technique used in this study is multiple linear regression to test the influence of independent variables on the dependent variable. The results of the study show that the t test (partial) Eresults for Experiential Marketing, E-Trust, and E-Security have a significant effect on customer loyalty, while E-Service Quality does not have a significant effect on customer loyalty. Meanwhile, the F test (simultaneous) results indicate that E-Service Quality, Experiential Marketing, E-Trust, and E-Security of BCA's E-Branch simultaneously affect customer loyalty. This research provides valuable insights for BCA to optimize factors influencing customer loyalty through eBranch services, particularly at KCP Gatot Subroto Malang. Keywords: E-Service Quality, Experiential Marketing, E-Trust, E-Security eBranch BCA, and customer loyalty